Bezrobocie i ubóstwo jako trudne problemy ekonomiczne i społeczne w województwie małopolskim na przykładzie powiatu tarnowskiego - Sadłoń, Maciej (My University, 2015)
Celem pracy jest przedstawienie bezrobocia i ubóstwa jako bardzo trudnych problemów ekonomicznych i społecznych zarówno dla osób nimi bezpośrednio dotkniętych jak też dla całego społeczeństwa i kraju. Są to problemy, które wzbudzają wielkie poruszenie, gdyż związane są z pozycją człowieka w społeczeństwie oraz z jego świadomością. W takiej sytuacji z pomocą przychodzi państwo działając przez instytucje państwowe i samorządowe. W pracy przedstawiono zakres bezrobocia i ubóstwa na przykładzie powiatu tarnowskiego oraz formy pomocy i przeciwdziałania tym zjawiskom. W pierwszej części zaprezentowano bezrobocie i ubóstwo jako jedne z głównych problemów społecznych. Dokonano charakterystyki problemu bezrobocia w aspekcie teoretyczno – metodologicznym oraz przedstawiono problem ubóstwa w świetle literatury przedmiotu, zaś na końcu tej części omówiono skutki bezrobocia i ubóstwa zarówno dla indywidualnej osoby jak i społeczeństwa. W kolejnej części pracy przedstawiono zjawisko bezrobocia i ubóstwa na terenie powiatu tarnowskiego, zaprezentowano strukturę bezrobocia i ubóstwa na terenie powiatu tarnowskiego w latach 2012 – 2014, problematykę przeciwdziałania powiatu.

The aim of the thesis is to present unemployment and poverty as very difficult economic and social problems both for the individuals directly affected as well as for society and the country. These are issues that make great excitement, as they are related to the position of a human in society and his or her awareness. In this case, the help is offered by the state and local institutions. The paper presents the scope of unemployment and poverty on the example of the district of Tarnow and the forms of help and preventing such phenomena. In the first part the unemployment and poverty are presented as one of the major social problems. There have been characteristics of the unemployment problem in theoretical - methodological aspects and there is presented the problem of poverty in the light of literature. At the end of this section the effects of unemployment and poverty, both for the individual person and society are discussed. In the next part of the paper the phenomenon of unemployment and poverty in the district of Tarnow is presented. The first general characteristics of the district of Tarnow is introduced. Sequentially statistical structure of unemployment and poverty in the district of Tarnow in the years 2012 – 2014 is described.
Unemployment and poverty as difficult economic and social problems in the Malopolska province on the example of the Tarnow district
Keywords: bezrobocie; ubóstwo; przeciwdziałanie bezrobociu; przeciwdziałanie ubóstwu; unemployment; poverty; preventing unemployment; preventing poverty